Корекція міопії та міопічного акстигматизму з використанням технології ReLEx SMILE - Завгородня, Наталія Григорівна; Поплавська, Ірина Олександрівна; Костровська, Катерина Олегівна; Zavgorodnya, N. H.; Poplavska, I. O.; Kostrovska, K. O (My University, 2024)
Мета - проаналізувати результати фемтосекундної лазерної технології ReLEx SMILE у пацієнтів з міопією та міопічним астигматизмом. The results of the femtosecond laser technology ReLEx SMILE in 250 patients (498 eyes) with myopia and myopic astigmatism were analyzed. Among them, 116 men (46.4%) and 134 women (53.6%) aged 18 to 40 years (average age 27.5 years). Mild myopia was noted in 221 eyes (44.3%), moderate in 188 (37.8%), in the rest – high myopia (89 eyes, 17.9%). It was found that the use of the ReLEx SMILE technology is a highly effective and low-traumatic intervention, it allows obtaining the maximum corrected visual acuity on the first day in 97.8% of patients, after 1 month in 98.6%.
Correction of myopia and myopic akstigmatism using ReLEx SMILE technology